Harmonisasi dan Sinkronisasi Hukum terhadap Perbedaan Pengaturan Barang Impor dalam Keadaan Baru - Leny Pratiwi (Fakultas Hukum Universitas Islam Indonesia, 2018)
The objectives of this study were to determine and examine the factors causing differences in the regulation of imported goods in the form of new goods as shown in the existing differences between the law and Regulation of the Minister of Trade with the Regulation of the Minister of Finance as well as the efforts to harmonize and synchronize the differences found in the regulations of imported new goods. This was a normative legal research, with statute approach. The results and discussion of this research showed that the factors causing the different arrangements of imported new goods are related to the background of the establishment of the legislations, namely the Trade Law, Regulation of the Minister of Trade No. 48/M-DAG/PER/7/2015, Regulation of the Minister of Trade No. 51/M-DAG/PER/7/2015, and Regulation of the Minister of Finance No. 6/PMK.010/PER/2017 and the fact that the theory of legal system is not implemented because such legal system contains the stages of the formulation of laws and regulations which include harmonization and synchronization among Pancasila, the 1945 Constitution, and legislation. Law is declared to be valid if it is sourced and based on norms established by higher norms, in this case the principle of lex superiori derogate legi inferiori. An effort to harmonize and synchronize the differences in the arrangement of imported new goods is to pay attention to the procedures for the establishment of legislation especially regarding the harmonization and synchronization stage that must be undertaken by the Directorate General of Legislation (DJPP)